2008
DOI: 10.1007/s11595-007-3386-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure, electrical conducting and thermal expansion properties of Ln0.6Sr0.4Co0.8Fe0.2O3 (Ln=La, Pr, Nd, Sm) ceramics

Abstract: Ln 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3 (Ln=La, Pr, Nd, Sm) perovskite-type complex oxides were synthesized using a glycine-nitrate process, and the structure, electrical conducting and thermal expansion properties of the resulting ceramics were examined with regard to the nature of the lanthanide cations. The results indicated that the La, Pr and Nd specimens had a rhombohedral symmetry, while an orthorhombic structure was determined for the Sm specimen. The pseudo-cubic lattice constant decreased with smaller lantha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…15 The degree of the orbital overlap is closely associated with the B-O-B bond angle. 16 The electrical conductivity for Gd 0.5 Sr 0.5 CoO 3 shows a transition from semiconducting to metallic behavior, that is, the conductivity starts to decrease from a high value with temperature instead of increase. This result is accordance with the report by Dyck.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…15 The degree of the orbital overlap is closely associated with the B-O-B bond angle. 16 The electrical conductivity for Gd 0.5 Sr 0.5 CoO 3 shows a transition from semiconducting to metallic behavior, that is, the conductivity starts to decrease from a high value with temperature instead of increase. This result is accordance with the report by Dyck.…”
Section: Resultsmentioning
confidence: 98%
“…[4][5][6][7] The properties of ABO 3 perovskite type oxides could be changed by either A or B-site doping. Tai et al 8,9 have found that the electrical properties of La 1Àx Sr x Co 1Ày Fe y O 3Àd is heavily dependent on x and y. Xu et al 10 have reported the rare earth elements Ln have a significant influence on the electrical properties of Ln 1Àx Sr x Co 0.2 Fe 0.8 O 3Àd . In the case of Sm 1Àx Sr x CoO 3Àd systems, Tu et al 11 reported that their electrical properties reach the highest value as x 5 0.5, while the electrical properties decrease with Fe doping in the B site.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, perovskite materials are strong candidates for developing ceramic-carbonate membranes for the selective separation of CO 2 at elevated temperatures. [21][22][23][24] For example, the ceramic oxide La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3-δ (LSCF) is one of the materials taken as a reference. Previously obtained results indicate that in a perovskite-type material, such as LSCF, the CO 2 separation follows the reaction mechanism (Equation 1).…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite‐type materials exhibit high oxygen‐ion diffusion rates through their crystalline structure and significant surface exchange kinetics under oxidizing conditions. Therefore, perovskite materials are strong candidates for developing ceramic‐carbonate membranes for the selective separation of CO 2 at elevated temperatures 21‐24 . For example, the ceramic oxide La 0.6 Sr 0.4 Co 0.8 Fe 0.2 O 3‑δ (LSCF) is one of the materials taken as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…Their researches focused mainly on achieving lower thermal expansion coefficient (TEC) values, at the same time, no decline in electrochemical properties [33][34][35][36][37]. Based on our preliminary study, it can be found that the bandwidth of the sintered undoped SSC is too small to use as microwave absorption materials despite with excellent infrared emissivity.…”
Section: Introductionmentioning
confidence: 99%